High photocatalytic activity of Cu2O embedded in hierarchically hollow SiO2 for efficient chemoselective hydrogenation of nitroarenes - Yin, Zhengliang; Xiao, Yingguan; Wan, Xiong; Jiang, Ying; Chen, Gang; Shi, Qingye; Cao, Shunsheng (Springer, 2020)
Photocatalytic organic conversion is a crucial process in the hydrogenation of nitroarenes, but harsh reaction conditions such as long reaction time, high hydrogen pressure, and organic medium still need to be considerably overcome under visible-light irradiation. Here, we have constructed a transition metal oxide photocatalyst by embedding low-cost Cu2O with strong visible-light absorption into hierarchically hollow SiO2 sphere (SiO2-Cu2O@SiO2) that can suppress the escape of photogenerated atomic hydrogen and promote the contact probability between hydrogen atom and nitroarene molecules due to confinement effect. Remarkably, the SiO2-Cu2O@SiO2 photocatalyst can exhibit efficient chemoselectivity toward the hydrogenation of various nitroarenes in an aqueous system at ambient conditions, successfully working out the requirement of strict hydrogenation conditions, especially for organic medium over almost all of the reported photocatalysts. Notably, quantitative aniline can be produced for the visible-light catalytic reduction of nitroarenes, suggesting a considerable potential for industrial application
Keywords: Hydrogenation of nitroarenes